Grocery retailing in Poland: Structural changes and foreign direct investment - Roland Herrmann; Anke Möser; Sascha A. Weber (Justus-Liebig-Universität Gießen, Zentrum für Internationale Entwicklungs- und Umweltforschung (ZEU), 2009)
The development of the Polish food retailing sector is very interesting. With the transition from a socialist to a market economy, structural change in the retailing sector has been especially rapid and the new open markets in Poland have attracted foreign investors throughout the economy in general and in the foodretailing sector in particular. This article describes and analyses the major trends in Polish food retailing. It is organised as follows. The structure of food retailing is described and explained in Section 2, first at the store-type level and then at the firm level. How the powerful concentration process in food retailing has affected the marketing chain is also discussed. Inward foreign direct investment (FDI) in Polish food retailing is covered in Section 3. Given the special importance of FDI in the Polish economy during the transition process, an analysis is carried out of the determinants of FDI in retailing within a cross-country dataset and with a particularly detailed look at FDI in Poland. The results are summarised in Section 5.
Keywords: 330; Lebensmitteleinzelhandel; Direktinvestition; Wirtschaftliche Anpassung; Branchenentwicklung; Polen